Kandungan Kapsaisin dan Dihidrokapsaisin Pada Berbagai Buah Capsicum - Sukrasno Sukrasno; Siti Kusmardiyani (Institut Teknologi Bandung, 1997)
Search for the hotest chilli pepper (Capsicum) fruits which was based on their capsaisinoid contents has been conducted. Chilli pepper fruits were collected from various places in Indonesia and two of them from Japan. From the 25 kinds of chilli pepper analysed, it was found that all C. frutescens contained capsaicinoids while in some C. annuum these compounds were not detected. Capsaicinoid content in chilli pepper fruits is affected by the their age and the highest content found in mature fruits before ripening which is indicated by the change of colour from green or pale yellow to red.